2020
DOI: 10.3855/jidc.13090
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a multimodal hand hygiene improvement strategy in Cambodian hospitals

Abstract: Introduction: Hand hygiene is the most effective method of preventing healthcare-associated infections. Healthcare-associated infections are considered serious in developing countries, and there are few reports on the hand-hygiene status of these countries. Thus, we evaluated hand-hygiene status in eight hospitals in Cambodia to understand and identify factors hindering effective infection control. Methodology: Eight infection-management instructors working in one of the eight Cambodian government hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
0
5
2
Order By: Relevance
“…The mean level of hand hygiene in our study was higher than that reported in Cambodia (HHSAF score = 178), India (HHSAF score = 225), and Tanzania (HHSAF score = 187) [ 25 , 26 , 27 ]. Unlike the health facilities in Cambodia, in which no hospital achieved an intermediate hand hygiene level [ 25 ], nine of the 13 hospitals in our study achieved an intermediate hand hygiene level. Sierra Leone is one of the countries in West Africa that has had high-risk infectious disease outbreaks, including the 2014/2016 Ebola virus disease epidemic [ 28 ].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The mean level of hand hygiene in our study was higher than that reported in Cambodia (HHSAF score = 178), India (HHSAF score = 225), and Tanzania (HHSAF score = 187) [ 25 , 26 , 27 ]. Unlike the health facilities in Cambodia, in which no hospital achieved an intermediate hand hygiene level [ 25 ], nine of the 13 hospitals in our study achieved an intermediate hand hygiene level. Sierra Leone is one of the countries in West Africa that has had high-risk infectious disease outbreaks, including the 2014/2016 Ebola virus disease epidemic [ 28 ].…”
Section: Discussioncontrasting
confidence: 83%
“…We have identified gaps that should be addressed to ensure further improvement and progress on hand hygiene promotion activities in Sierra Leone. First, there are gaps in the provision of continuous supplies of soap and running water, as well as the availability of single-use towels for hand drying, similar to Cambodia [ 25 ]. This is due to a lack of practical plans and dedicated budgets to improve hand hygiene infrastructure and maintain these supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous hand hygiene studies in Cambodia have employed the use of self-reported behaviour and proxy measures of handwashing behaviour to assess HCW hand hygiene practices [ 26 , 27 , 44 , 45 ]. Self-reporting is not recommended as a reliable method to assess handwashing behaviour due to over-reporting, and proxy measures do not accurately reflect the actual handwashing practice [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings are consistent with a recent systematic review of birth attendants’ hand hygiene compliance in health facilities in LMIC that estimated low compliance rates ranging between 1.3% and 38% [ 14 ]. Facility-based hand hygiene studies in Cambodia similarly found practices across all staff levels in various HCF departments [ 44 , 45 ] and specifically among midwives during newborn post-natal care [ 26 , 27 ] to be suboptimal and were influenced by a lack of adequate training, basic infrastructure and poor implementation of multimodal hand hygiene improvement strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that increasing psychological cues and simplifying operational methods can enhance medical workers’ compliance with hand hygiene protocols. 13–17 In line with these findings, it is suggested that hospitals place hand hygiene posters in prominent locations and provide ample, user-friendly hand hygiene facilities for medical personnel. (4) Regular and unannounced hand hygiene inspections are essential to ensure compliance.…”
Section: Discussionmentioning
confidence: 89%